An innovation on clinical placement for occupational therapy mental health during the COVID-19: a mixed-methods feasibility study - Wan Yunus, Farahiyah; Romli, Muhammad Hibatullah; Mohd Rasdi, Hanif Farhan; Harun, Dzalani; Kadar, Masne (Frontiers Media, 2022)
The COVID-19 pandemic altered the health profession's education. Educational activities were shifted to online, and clinical placements were compromised in certain countries. A mixed-methods study included 17 undergraduates undergoing a mental health placement. The first 3 weeks of clinical placement applied online case-based learning in written and in video format. The last 2 weeks involved hybrid remote and physical onsite clinical placement. SPICES model utilizing various active learning activities, case studies and client attendance, facilitator engagement, discussion and feedback were implemented. A self-administered System Usability Scale (SUS), e-learning preference level, focus group discussion, and reflective writing was conducted at the end of each week and the students' final marks were compared with the past cohort who attended conventional physical clinical placement. Two-way mixed ANOVA indicates no significant interaction was found on the SUS (p = 0.062, η2p = 0.062) and preference scores (p = 0.285, η2p = 0.079) according to week and practical site. There was no significant difference in the final mark among the online and onsite placement of the current cohort (p = 0.350, d = 0.47). The current cohort reported better marks than the previous cohort who attended conventional placement (p = 0.006, d = 0.99). Qualitative findings show positive responses where online activities have minimal restriction on the learning process. This innovative approach is acceptable for substituting conventional clinical learning during this restricted situation.